Organising for growth: Irish state administration 1958-2008 - Hardiman, Niamh; MacCarthaigh, Muiris (Economic & Social Studies, 2010)
This paper analyses some key features of Irish public administration as it has developed since the foundation of the state, paying particular attention to the period from the late 1950s onward. During these decades, notwithstanding successive waves of concern expressed over the need for public sector reform, the evidence suggests an underlying lack of coherence in the evolution of the public administration system that resulted in a poor capacity for effective policy coordination. Yet the drive toward economic modernisation also resulted in the creation of new state competence to support industrial development both directly and indirectly. These changes can be tracked organisationally, drawing on the database of the IRCHSS-funded Mapping the Irish State project.
Keywords: Public administration; Ireland; Modernisation; Economic development